41 Is HPV infection the first genetic hit in head and neck cancer?. Issue 5 (May 2015) - Rietbergen, M.M.; ,; Bloemena, E.; Leemans, C.R.; Brakenhoff, R.H.
Abstract : Introduction: Besides smoking and excessive consumption of alcohol, infection with the human papillomavirus (HPV) is an accepted risk factor for head and neck cancer. HPV-positive tumors are molecularly distinct from HPV-negative tumors. Moreover, HPV-positive oropharyngeal squamous cell carcinomas (OPSCC) have a better prognosis than patients HPV-negative OPSCC. Important factors contributing to this better prognosis are relatively low numbers of local/regional recurrences (LRR) and second primary tumors (SPT) in patients with HPV-positive OPSCC. These low numbers may be explained by the absence of 'field cancerization', which is a cause of LRR and SPT in patients with HPV-negative OPSCC. We aimed to detect 'field cancerization' in patients with HPV-positive OPSCC. We assumed that HPV is involved in the early stage of carcinogenesis in OPSCC as it is in cervical carcinogenesis, and its presence could therefore be considered a reliable marker for the detection of HPV-infected fields. Therefore, the mucosa surrounding HPV-positive OPSCC was analyzed for HPV viral transcripts. Materials and methods: We included 20 patients who were surgically treated for an HPV-positive OPSCC in the period 2000–2006. Of each patient, the formalin-fixed paraffin-embedded tumor sample and all available resection margins were collected. In total, 97 resection margins were investigated with an average of five resection margins per tumor. All samples were analyzed for the presence of tumor and the presence of transcriptionally active HPV by HPV16-E6-mRNA detection. Results: All tumors were HPV16-E6-mRNA positive. HPV16-E6-mRNA could be detected in the resection margins that contained tumor ( n = 6). All tumor negative resection margins ( n = 91) scored negative for HPV16-E6-mRNA. Conclusions: Transcriptionally active HPV could not be detected in the mucosa surrounding an HPV-positive OPSCC, which suggests the absence of field cancerization. This observation may explain the lower number of LRR and SPT in patients with HPV-positive OPSCC. Alternatively, we may hypothesize that HPV-infection is not the first genetic or epigenetic change as it is in cervical cancer.